2016
DOI: 10.4103/1008-682x.188448
|View full text |Cite
|
Sign up to set email alerts
|

Sperm subpopulations in avian species: a comparative study between the rooster (Gallus domesticus) and Guinea fowl (Numida meleagris)

Abstract: The main aims of this research were to study possible differences in objective morphometric sperm characteristics, establish normative sperm morphometry standards, and evaluate the presumed different subpopulation distribution of avian spermatozoa from the rooster (Gallus domesticus) and Guinea fowl (Numida meleagris) as model avian species. Seventy-two ejaculates (36 per species studied) were obtained manually, following a training period involving gently combined dorso-abdominal and lumbo-sacral massage of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…By integrating the original variables according to their coherence in a database into a new complex mathematical variable, clearly defined homogeneous subpopulations of spermatozoa can be defined. In support of the theory above, the papers presented here showed that most of the variance from up to 13 morphometric variables could be explained by only two or three PCs: two in bulls,16 adolescent humans,8 adult human sperm head DNA,9 domestic cats,10 puma,11 roosters, and guinea fowls12 and three PCs in adult human split ejaculate samples 7…”
Section: The Significance Of the Morphometric Analysis Of Sperm Cellssupporting
confidence: 81%
See 2 more Smart Citations
“…By integrating the original variables according to their coherence in a database into a new complex mathematical variable, clearly defined homogeneous subpopulations of spermatozoa can be defined. In support of the theory above, the papers presented here showed that most of the variance from up to 13 morphometric variables could be explained by only two or three PCs: two in bulls,16 adolescent humans,8 adult human sperm head DNA,9 domestic cats,10 puma,11 roosters, and guinea fowls12 and three PCs in adult human split ejaculate samples 7…”
Section: The Significance Of the Morphometric Analysis Of Sperm Cellssupporting
confidence: 81%
“…Here, the number of subpopulations ranged from two to five: two (for the X-/Y-bearing bovine sperm heads,15 for large+elongated/small+elongated sperm heads in human adolescents8), three (for large+round/elongated/small spermatozoa in human sperm heads in split ejaculate fractions,7 for elongated+intermediate/large+high acrosome/short+small sperm heads in the puma,11 for small, wide and slightly elliptical/average size, long, narrow and very elliptical/very large, wide and elliptical sperm heads in the rooster12), four (for large/high medium/low medium/small in human sperm head DNA,9 for small/short/large/narrow sperm heads in the bull,14 for shape-related sperm heads in both normo- and terato-zoospermic cats10) to five (for very small, wide, very short and slightly elliptical/small, very short, very wide and slightly elliptical/very large, very wide, short and slightly elliptical/average size, very long, very narrow and very elliptical/average size, long, narrow and elliptical sperm heads in the guinea fowl12). …”
Section: The Significance Of the Morphometric Analysis Of Sperm Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, our additional analysis of using a paired t -test confirmed our results from linear mixed models and was restricted to males for which we collected faecal and massage samples during both events, so here males served as their own control. Therefore, the observed sperm size differences in heads and midpieces between methods might be explained by sperm in faeces resembling a different subpopulation of sperm within males and could be indicative of differences in the degree of post-meiotic sperm maturation [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In human's sperm, two (Vásquez et al, 2016) or three Yániz et al, 2016) morphometric subpopulations were observed. In other species, a different number of subpopulations were identified; for example, three for pumas (Cucho et al, 2016) and roosters (García-Herreros, 2016), four for cats (Gutiérrez-Reinoso & García-Herreros, 2016), and five for guinea fowls (García-Herreros, 2016). Following the observed motility, each animal inside the same species showed a different subpopulation frequency, probably a consequence of its particular genetic and physiological build.…”
Section: Principal Components Analysismentioning
confidence: 99%